Pengaruh Gaya Hidup dan Locus of Control terhadap Financial Management Behavior pada Mahasiswa Universitas Islam Bandung - Salma Daaniyah Juanda; Handri (Bandung Conference Series: Business and Management, 2022)
Abstract . The purpose of the study was to find out how much influence the Lifestyle and Locus of Control I had on Financial Management Behavior partially and simultaneously on management students of the 2018 Islamic University of Bandung, because of the phenomenon of students' financial problems who spent more than their pocket money, resulting in students need to have student financial management behavior that must be able to be improved. By improving personal finances, managing and controlling income and expenses, as well as paying attention to Lifestyle and exercising self-control to implement good Financial Management Behavior, by conducting research to find out how the Lifestyle, Locus of Control, Financial Management Behavior of students management of the 2018 Islamic University Bandung until financial problems can occur. The research was carried out using a deductive quantitative method. The population selected was management students of the 2018 Islamic University of Bandung. Sampling is a random method of 168 respondents. The data used is primary data Ilikert scale 1-5 data collection through questionnaires to respondents. The data analysis technique is the analysis of the coefficient of determination using SPSS 25. So it can be concluded that partially and simultaneously there is a significant influence between Lifestyle and Locus of Control on Financial Management Behavior. the effect simultaneously is 54.20% while the remaining 45.80% is influenced by other variables not found in the study. Abstrak - Tujuan dari penelitin agar mengetahui seberapa besar pengaruh dari Gaya Hidup dan Locus of Control terhadap Financial Management Behavior secara parsial dan simultan pada mahasiswa manajemen Angkatan 2018 Universitas Islam Bandung, karena adanya fenomena mengenai masalah keuangan mahasiswa yang melakukan pengeluaran lebih besar dibandingkan uang saku yang dimiliki, sehingga mengakibatkan mahasiswa perlu memiliki perilaku pengelolaan keuangan mahasiswa yang harus mampu diperbaiki. Dengan cara memperbaiki keuangan pribadi, melakukan pengelolaan dan pengendalian terhadap pendapatan dan pengeluaran, serta memperhatikan Gaya Hidup dan melakukan kontrol diri untuk mengimplementasikan Financial Management Behavior yang baik, dengan melakukan penelitian agar mengetahui bagaimana Gaya Hidup, Locus of Control, Financial Management Behavior mahasiswa manajemen Angkatan 2018 Universitas Islam Bandung sampai dapat terjadi masalah keuangan, Penelitian dilakukan menggunakan metode kuantitatif bersifat deduktif. Populasi yang dipilih adalah mahasiswa manajemen Angkatan 2018 Universitas Islam Bandung. Penarikan sampelnya yaitu metode random sebanyak 168 responden. Data yang digunakan yaitu data primer skala likert 1-5 pengumpulan data melalui kuisioner kepada responden Teknik analisis data yaitu analisis koefisien determinasi menggunakan SPSS 25. Sehingga dapat disimpulkan secara parsial dan simultan adanya pengaruh signifikan antara Gaya Hidup dan Locus of Control terhadap Financial Management Behavior. pengaruhnya secara simultan sebesar 54,20% sedangkan sebesar 45,80% sisanya dipengaruhi variabel lain yang tidak terdapat dipenelitian.